Policy Model for Zakat Management in Batang Regency: Analysis and Implementation - Naim, Abdul Haris; Maarif, Muhamat Nur (Sharia Faculty Islamic Economic Law Study Department, 2025)
This research examines the zakat management policy model in Batang Regency with a focus on existing system analysis and its implementation. This study is motivated by several cases of zakat fund misappropriation by employees, indicating weaknesses in the supervision and management systems. BAZNAS in Batang Regency as a non governmental institution currently relies on the SIMBA system (Zakat Bazis Management System) and has not implemented PSAK No. 109 as the zakat accounting standard. This research uses a qualitative approach with data collection methods through interviews, observations, and document analysis. The results show that zakat management in Batang Regency requires a policy model reform that emphasizes transparency, accountability, and professionalism. This research recommends the adoption of PSAK No. 109 as a zakat accounting standard, strengthening internal and external monitoring systems, and modernizing the management information system to prevent misappropriation and increase public trust. The implementation of the proposed policy model is expected to improve the effectiveness of zakat management and maximize the socio-economic impact of zakat funds collected in Batang Regency.